Adventures with Land Animals - Kwek, Karen (Singapore : WS Education, an imprint of World Scientific Publishing Co. Pte. Ltd., 2022)
Adventures with Land Animals is an immersive encounter with more than 20 residents of diverse habitats on - and below! - the ground. Why should you appreciate the earthworm? What's the ring-tailed lemur trying to say? What makes the Serengeti wildebeest cross crocodile-infested waters? Roam Christmas Island with the red crab. Stay clear of the kangaroo's powerful kick. And swing in the treetops with the white-handed gibbon! From icy mountains to arid deserts, and from dense forests to open grasslands, experience the spectacular world of land animals as never before!
Keywords: Grassland animals -- Comic books, strips, etc; Grassland animals -- Juvenile literature; Grassland animals -- Behavior -- Comic books, strips, etc; Grassland animals -- Behavior -- Juvenile literature; Graphic novels; Comic books, strips, etc